STRUKTUR DAN KOMPOSISI JENIS KOMUNITAS BURUNG DI LAHAN PERTANIAN KAWASAN HUTAN LINDUNG GUNUNG MAHAWU SULAWESI UTARA - Alfons Patandung; Johny S. Tasirin; Alfonsius Thomas; Reynold P. Kainde (COCOS, 2014)
ABSTRACTMount Mahawu Forest Reserve is a protected area situated in the city of Tomohon and regency of Minahasa,North Sulawesi province. In year 2004 Birdlife International established Mount Mahawu Forest Reserve as an Important Bird Area. One particular habitat of bird colonies in Mount Mahawu Forest Reserve is agricultural land.This research aims to create an inventory of and analyze the species diversity of bird communities in agricultural land surrounding Mount Mahawu Forest Reserve, North Sulawesi. This research was carried out on September to October 2013 in Mount Mahawu Forest Reserve, North Sulawesi. This research used the point count method.There are 32 bird species from 16 families and 9 orders. The number of individuals found inhabiting agricultural land was 198 individuals. Out of the species observed inhabiting agricultural land, 9 species or 28,1 % of the total number of species are species endemic to Sulawesi.The most abundant species isthe Glossy Swiftlet (Collocalia esculenta) with 45 individuals and relative abundance score of 22,72 %.The diversity index of agricultural land habitats is 2,92, while the evenness index is 0,87.Keywords: Birds, Mount Mahawu Forest Reserve, Species diversity